2003
DOI: 10.1002/biof.5520190104
|View full text |Cite
|
Sign up to set email alerts
|

ADP‐ and oligomycin‐sensitive redox behavior of F0 b thiol in ATPsynthase depends on neighbored primary structure: Investigations using 14‐C‐labeled alpha lipoic acid

Abstract: Purified ATPsynthase of bovine heart mitochondria has been analyzed for its mobility and reactivity of oligomycin-sensitive sulfhydryl regions in presence of the substrate ADP and oligomycin. Labeling of thiol groups at the hydrophobic F_0 region of the ATPsynthase was increased in the enzyme initially treated with SDS, N-ethylmaleimide and dithiothreitol (modified enzyme). After dialysis or gel permeation the ATPsynthase was treated with [14C] alpha lipoic acid at a molar ratio of 35-85/1 (lipoic acid/ATPsynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…ATP synthesis occurs only if the dithiols between the F1 and the F 0 j part of the enzyme remain functional (27). The lipophilic character of LA allows it to reach the inner membrane of the mitochondrion and to enhance mobility and integrity of the enzyme (28). ATP synthesis may therefore also occur under conditions of ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…ATP synthesis occurs only if the dithiols between the F1 and the F 0 j part of the enzyme remain functional (27). The lipophilic character of LA allows it to reach the inner membrane of the mitochondrion and to enhance mobility and integrity of the enzyme (28). ATP synthesis may therefore also occur under conditions of ischemia/reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism which could enable LA to influence the prevention of caspase-9 activation, or the release of cytochrome c , remains a matter of speculation. Previous studies have, however, demonstrated that LA interacts directly with an essential enzyme of the respiratory chain, enabling the amino acid to maintain its integrity and function [25] . A further cause for the rise in caspase-3 activity may be an increase in the LPO level in liver tissue in the early phase of IRI [26] .…”
Section: Discussionmentioning
confidence: 99%
“…We recently described similar effects of LA in the IL after ischemia/reperfusion [19] . Moreover, the lipophilic character of LA allows it to reach the membrane of mitochondria [24] . Under these conditions, LA increases production of ATP in vitro.…”
Section: Discussionmentioning
confidence: 99%